Analysis of Two-layered Blood Flow through Artery with Mild Stenosis - Pokhrel, Puskar R. (Humanities and Social Sciences Journal, 2021)
Employing the Navier-Stokes equations, and considering the blood flow in an artery in an axi-symmetric form, the blood flow dynamics in cylindrical artery are analyzed by evaluating pressure, pressure drop against the wall, shear stress on the wall. Plasma and core layers are considered in the blood flow in cylindrical artery with mild stenosis. It is analyzed the volumetric rate of blood flow in plasma and core layers of the cylindrical shape artery. It is also observed the pressure gradient on the surface of the stenosis in both layers. The dynamics of blood are analyzed by evaluating the ratio of shear stresses of the surface of stenosis with the radius of the artery.